The effect of chrysin–curcumin-loaded nanofibres on the wound-healing process in male rats. Issue 1 (4th December 2019) - Mohammadi, Zoheyr; Sharif Zak, Mohsen; Majdi, Hasan; Mostafavi, Ebrahim; Barati, Meisam; Lotfimehr, Hamid; Ghaseminasab, Kambiz; Pazoki-Toroudi, Hamidreza; Webster, Thomas J.; Akbarzadeh, Abolfazl
Abstract: Aim: The aim of the present study was to produce chrysin–curcumin-loaded PCL-PEG nanofibres by an electrospinning technique and to evaluate the biological activity of the chrysin–curcumin-loaded PCL-PEG fibres for wound healing and its related genes using in vivo methods. Materials and methods: The electrospinning method was carried out for the preparation of the chrysin, curcumin and chrysin–curcumin-loaded PCL-PEG nanofibres with different concentrations. FTIR and SEM were performed to characterize the chemical structures and morphology of the nanofibres. In vitro drug release, as well as in vivo wound-healing studies were investigated in male rats. The expressions of genes related to the wound-healing process were also evaluated by real-time PCR. Results: Our study showed that the chrysin–curcumin-loaded nanofibres have anti-inflammatory properties in several stages of the wound-healing process by affecting the IL-6, MMP-2, TIMP-1, TIMP-2 and iNOS gene expression. Our results demonstrated that the effect of the chrysin-loaded nanofibre, the curcumin-loaded nanofibre and the chrysin–curcumin-loaded nanofibre in the wound-healing process is dose dependent and in accordance with the obtained results in that it might affect the inflammation phase more than the other stages of the wound-healing process. Conclusion: We have introduced chrysin–curcumin-loaded PCL-PEG nanofibres as a novel compound for shortening the duration of the wound-healing process.